Radar backscatter measurements from RADARSAT SAR imagery of South Pole Station, Antarctica - Hong-Gyoo Suhn; Jezek, K.; Baumgartner, F.; Forster, R.; Mosley-Thompson, E. (1999 IEEE International Geoscience and Remote Sensing Symposium, 1999)
Ice sheet backscatter around South Pole Station was measured from several different azimuthal angles using RADARSAT-1 SAR data. The authors observed strong azimuthal anisotropy (3-4 dB) between radar look directions across and along the prevailing wind direction. They speculate that the azimuthal variation of backscatter around the South Pole area may be largely attributed to systematically oriented sastrugi and buried sastrugi. Radar backscatter is well correlated with surface topography over a spatial wavelength band of 15 to 20 km. They propose that grain size variations control backscatter patterns associated with undulating surface topography.